2023
DOI: 10.3390/genes14071486
|View full text |Cite
|
Sign up to set email alerts
|

Presence of Human DNA on Household Dogs and Its Bi-Directional Transfer

Abstract: Awareness of the factors surrounding the transfer of DNA from a person, item, or surface to another person, item, or surface is highly relevant during investigations of alleged criminal activity. Animals in domestic environments could be a victim, offender, or innocent party associated with a crime. There is, however, very limited knowledge of human DNA transfer, persistence, prevalence, and recovery (DNA TPPR) associated with domestic animals. This pilot study aimed to improve our understanding of DNA TPPR as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Similarly, Reither et al [67] investigated two possible scenarios, demonstrating that an indirect DNA transfer could occur from clothing to flooring and from flooring to clothing in both 'active' and 'passive' situations, even if the DNA transfer was greater in active simulation. Interestingly, Monkman et al [70] demonstrated that a domestic animal (in their experimental model they used a dog) could be a vector for human DNA transfer, demonstrating a transfer from the animal to a gloved hand during patting and a bed sheet while walking.…”
Section: Main Findingsmentioning
confidence: 99%
“…Similarly, Reither et al [67] investigated two possible scenarios, demonstrating that an indirect DNA transfer could occur from clothing to flooring and from flooring to clothing in both 'active' and 'passive' situations, even if the DNA transfer was greater in active simulation. Interestingly, Monkman et al [70] demonstrated that a domestic animal (in their experimental model they used a dog) could be a vector for human DNA transfer, demonstrating a transfer from the animal to a gloved hand during patting and a bed sheet while walking.…”
Section: Main Findingsmentioning
confidence: 99%